Islamic Banks Performance: An Assessment using Sharia MaqashidIndex, Sharia Conformity and Profitability and CAMELS - Mokhamad Ikhsan Ramdhoni; Firdaus Ahmad Fauzi (Politeknik Negeri Bandung, 2020)
Indonesian Islamic banking system has existed for more than 25 years old. However, at this age, it still has not had its own instrument for measuring performance and still adopts the orthodox measuring instrument which is restricted to financial ratio measurement only. The use of this orthodox measuring instrument as the only tool to evaluate the Islamic banks performance is considered less suitable, both in terms of the features and the purposes of Islamic banking in general. Therefore, this study aims to evaluate the performance of Islamic banks using the Sharia Maqashid Index, Sharia Conformity and Profitability (SCnP) and CAMELS approaches. The population of this study was all Islamic Commercial Banks listed in Bank Indonesia from 2012-2016, while the data analysis technique used the quantitative research with descriptive approach. The Sharia Maqashid Index approach has three variables; educating people, establishing justice, and achieving public interest. The Sharia Conformity and Profitability (SCnP) approach has two variables; Sharia Conformity and Profitability. Meanwhile, the CAMELS approach has five variables; Capital, Asset Quality, Management, Earning, and Liquidity. The results of the research using the Sharia Maqashid Index approach shows that Bank Muamalat is in the first rank, followed by Bank Syariah Mandiri, BNI Syariah, and Bank Mega Syariah. By using the SCnP approach, the research shows that there are no Islamic banks in the upper right quadrant that has high sharia suitability and high profitability. Moreover, the CAMELS approach shows that all Islamic banks are quite healthy. The application of these performance measurement approaches become a factor that plays a dual role for the achievement of financial performance and sharia conformity.